The Influence of Digital Learning Tools on Students' Engagement in Secondary Schools: The Comparative Case Study in Azerbaijan - Taghiyeva, Dilara (My University, 2026)
This is a mixed-methods, comparative case study that explores the influence of digital learning tools on students’ engagements in secondary education in Azerbaijan and compares one regular public secondary school and one STEAM-focused public secondary school. Grounded in two theoretical frameworks, Technology Acceptance Model (TAM) and Student Engagement Model (SEM), the study explores how students’ perceptions of ease of use and usefulness of digital learning tools relate to their emotional, behavioral, and cognitive engagement. The research questions investigate the influence of the use of digital learning tools on students’ engagement in the regular public secondary and the STEAM-focused public secondary schools and identify the factors influencing this relationship in both schools. To address these questions, quantitative and qualitative data collected through student surveys (n=70), teacher interviews (n=4), and classroom observations (n=4) were integrated. The findings suggest that the use of digital learning tools has a positive influence on students’ multidimensional engagement, reflected on their interest, participation, and understanding. The factors influencing students’ engagement in lessons involving digital tools include infrastructure, digital divide, technological access, and teacher preparedness. The findings also revealed some challenges and concerns, such as Internet access, technical problems, screen fatigue, and student distraction. The discussion of the findings demonstrates that the use of digital learning tools can increase students’ engagement if implemented effectively by creating equitable access to technology and meaningful pedagogical approaches. To achieve this, the study also recommends enhancing teacher training through Continuing Professional Development opportunities, and addressing infrastructural inequities, particularly those between differing regions.
Keywords: Digital Learning Tools; Emotional Engagement; Behavioral Engagement; Cognitive Engagement; STEAM Schools; Secondary Education